2014
DOI: 10.1177/0148607114552848
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Slow Enteral Feeding Protocol and the Incidence of Necrotizing Enterocolitis in Extremely Low Birth Weight Infants

Abstract: An SSEF protocol significantly reduces the incidence of NEC and combined NEC/death in infants with birth weight <750 g. Despite taking longer to achieve full enteral feeding on this protocol, surviving ELBW infants demonstrated comparable weight gain at discharge without prolonging their hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 41 publications
1
26
1
7
Order By: Relevance
“…This contrasts data by Viswanathan et al, who reported that a slow standardized enteral feeding protocol reduced the incidence of NEC in infants < 750 g . Infants began enteral feedings at roughly 14 days of life and were then slowly advanced to full enteral feedings by 44–52 days of life . Based on our data, study infants < 750 g achieved enteral feedings earlier than the collective group of epoch 1 infants (median of 22 days).…”
Section: Discussioncontrasting
confidence: 94%
“…This contrasts data by Viswanathan et al, who reported that a slow standardized enteral feeding protocol reduced the incidence of NEC in infants < 750 g . Infants began enteral feedings at roughly 14 days of life and were then slowly advanced to full enteral feedings by 44–52 days of life . Based on our data, study infants < 750 g achieved enteral feedings earlier than the collective group of epoch 1 infants (median of 22 days).…”
Section: Discussioncontrasting
confidence: 94%
“…In the literature, the concept of slow advancements in enteral feeding volumes and consequently an increased number of parenteral nutrition days demonstrated no significant alterations in the overall incidence of NEC except in infants with a birth weight < 750 g [23]. In contrast to the number of parenteral feeding days, the velocity of enteral feeding volume expansion during the first postnatal week was not associated with the development of NEC.…”
Section: Discussionmentioning
confidence: 94%
“…Early feedings appear safe in these infants yet some feeding protocols involve the withholding of initial feedings for 7-14 d in ELBW infants (32). Slow feeding advances delay enteral provisions even if a mother's milk DHA concentration happens to be high.…”
Section: Articlesmentioning
confidence: 99%